The Substitution Effect on Reaction Enthalpies of Antioxidant Mechanisms of Juglone and Its Derivatives in Gas and Solution Phase: DFT Study - Aymard Didier Tamafo Fouegue; Désiré Bikélé Mama; Julius Numbonui Ghogomu; Younang Elie; Marie-Annie Etoh (Journal of Chemistry)
We examined the structure-reaction enthalpies-antioxidant activity relationship of the molecule library built around juglone and its derivatives at B3LYP/6-31+G(d,p) level. Three major antioxidant mechanisms (hydrogen atom transfer (HAT), single electron transfer-proton transfer (SET-PT), and sequential proton loss electron transfer (SPLET)) have been investigated in five solvents and in the gas phase. The delocalization of the unpaired electrons in the radicals or cation radicals has been explored by the natural bond orbital analysis and the interpretation of spin density maps. The results obtained have proven that the HAT mechanism is the thermodynamically preferred mechanism in the gas phase. But, in the solution phase, the SPLET mechanism has been shown to be more predominant than HAT. The reactivity order of compounds towards selected reactive oxygen species has also been studied.